NORMATIVITAS PERANG DALAM ISLAM - Widhiyoga, Ganjar (JPP (Jurnal Politik Profetik), 2013)
Fight in the way of Allah is not a fight against certain tribe, community or country. This kind of fight is against the way of human thought and behavior which denying the concept of mercy to the entire world (rahmatan lil alamin). When the way of thinking and behaving has changed, the fight is no longer valid and it then should be stopped. Besides, the fight against oppression and tyranny is not merely the responsibility of the oppressed, of certain tribe, community or country. Fight in the way of Allah against the oppression and tyranny is obliged to all human beings who are willing to realize the divine mercy to the entire world. This fight has to be consistently supported until oppression and tyranny have faded away and be changed to justice.